2017
DOI: 10.1002/qua.25458
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty quantification in theoretical spectroscopy: The structural sensitivity of X‐ray emission spectra

Abstract: We present a methodology for analyzing the dependence of molecular spectra calculated with quantum-chemical methods on the underlying molecular structure. This analysis is applied to investigate the structural sensitivity of calculated valence-to-core X-ray emission (VtC-XES) spectra for the test case of three iron carbonyl complexes, Fe(CO) 5 , [FeCp(CO) 2 (THF)] 1 (Cp 5 cyclopentadienyl, THF 5 tetrahydrofuran), and Fe(CO) 3 (cod) (cod 5 cyclooctadienyl). Based on this analysis, we discuss how the VtC-XES spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…27,[29][30][31] Here, we aim at systematically quantifying a further source of uncertainty, namely the dependence of s(E; R) on the input molecular structure. 35 The structural sensitivity presents a challenging case because the calculated spectrum depends on a rather large number of independent parameters (i.e., the nuclear coordinates R). In this respect, it fundamentally differs from, e.g., uncertainties due to approximation in the quantum-chemical model, which are usually related to only a few parameters.…”
Section: R !mentioning
confidence: 99%
“…27,[29][30][31] Here, we aim at systematically quantifying a further source of uncertainty, namely the dependence of s(E; R) on the input molecular structure. 35 The structural sensitivity presents a challenging case because the calculated spectrum depends on a rather large number of independent parameters (i.e., the nuclear coordinates R). In this respect, it fundamentally differs from, e.g., uncertainties due to approximation in the quantum-chemical model, which are usually related to only a few parameters.…”
Section: R !mentioning
confidence: 99%
“…This linear structural sensitivity can be calculated by numerical differentiation, i.e., by calculating the spectrum for displaced molecular structures [35]. Here, we employ a symmetric two-point formula [see Eq.…”
Section: Identification Of Influential Structural Distortionsmentioning
confidence: 99%
“…As an example, we consider the structural sensitivity of the calculated XES spectrum of Fe(CO) 5 . For this example, we already explored the dependence on manually selected structural distortions in our previous work [35]. An in-depth experimental and computational study of the XES spectrum of Fe(CO) 5 can be found in Ref.…”
Section: Identification Of Influential Structural Distortionsmentioning
confidence: 99%
See 2 more Smart Citations